The promise and the blessing : a historical survey of the Old and New Testaments - Harbin, Michael A. (Grand Rapids, Mich. : Zondervan, 2005)
"A historical survey of the Old and New Testaments of the Bible"--Provided by publisher.
The origin of the Bible -- This is the way the world was -- Why the world is such a mess -- Abraham and son(s) -- Jacob and his tribes -- Let my people go! -- Making a nation out of a mob -- Just a-lookin' for a home -- Joshua fit the battle of Jericho-- and Hazor too -- The best of times, the worst of times -- Give us a king like the rest of the nations -- A kingdom united -- The failure of the north -- The roller-coaster south -- The nation in exile -- Home again -- The blessing -- Bridges to the New Testament -- Who is Jesus the Messiah? -- An empty tomb -- The first church was Jewish -- Reaching out to gentiles -- What about the gentiles? -- Moving into Europe -- Tentmaker and troubleshooter -- The road to Rome -- Rome and beyond -- The end of the apostolic age -- But what about John?
Includes bibliographical references (p. 601-606) and index.
Keywords: Bible -- History of Biblical events -- Textbooks